Representasi Islam di Media Sosial dan Implikasinya terhadap Pendidikan Agama Islam - Agustin, Maulid; Nuha, Nazahah Ulin (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
The development of social media has transformed the way Islamic teachings are disseminated and represented, presenting both opportunities and challenges for Islamic Religious Education (PAI) teaching. Diverse representations of Islam in the digital space have the potential to strengthen moderate understanding, but also give rise to radical content that can lead to misconceptions among students. This study aims to analyze the dynamics of Islamic representation in social media and its implications for developing an PAI curriculum responsive to the digital era. The research was conducted using qualitative methods through a literature review and content analysis of various literature, social media content, and relevant documents. The results indicate that social media has a significant influence in shaping students' religious perceptions and opening up opportunities for creative da'wah (Islamic outreach), but it has also become a medium for the spread of intolerance and radicalism. Therefore, strengthening digital literacy, critical thinking skills, and the value of religious moderation is essential through an updated PAI curriculum. The integration of social media literacy materials into PAI can equip students to be more selective, tolerant, and adaptive in dealing with the flow of religious information in the digital era. This study emphasizes the strategic role of religious education in shaping a generation of Muslims who are both religious and and digitally literate.